2008
DOI: 10.1097/qad.0b013e3282f736f4
|View full text |Cite
|
Sign up to set email alerts
|

Early events in HIV transmission through a human reconstructed vaginal mucosa

Abstract: For the first time, we documented that, within 4 h following contact with HIV-infected cells, translocation of free HIV particles across a pluristratified mucosa is not detectable and that, in this context, it seemed that Langerhans cells do not increase HIV transmission. Moreover, we provided a useful model for the development of strategies preventing HIV entry into the female genital tract, especially for testing the efficiency of various microbicides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 40 publications
2
31
0
4
Order By: Relevance
“…57 In contrast, a recent study was unable to detect translocation of HIV-1 in reconstructed human vaginal mucosa, and presence of Langerhans cells did not alter HIV-1 transmission. 58 These studies suggest that the main target cells for HIV-1 are CD4 + DCs and T cells in the lamina propria of genital mucosa. Consequently, the enriched population of CD4 + T cells and APCs present in the transformation zone, where the ectocervix transitions into the endocervix, may be a particularly susceptible site for HIV entry.…”
Section: Hiv Interactions With Epithelial Barrier and Target Cells Inmentioning
confidence: 99%
“…57 In contrast, a recent study was unable to detect translocation of HIV-1 in reconstructed human vaginal mucosa, and presence of Langerhans cells did not alter HIV-1 transmission. 58 These studies suggest that the main target cells for HIV-1 are CD4 + DCs and T cells in the lamina propria of genital mucosa. Consequently, the enriched population of CD4 + T cells and APCs present in the transformation zone, where the ectocervix transitions into the endocervix, may be a particularly susceptible site for HIV entry.…”
Section: Hiv Interactions With Epithelial Barrier and Target Cells Inmentioning
confidence: 99%
“…The mechanism of HIV transmission across the mucosa still remains an unresolved enigma, despite outstanding studies that have already shed light on relevant issues (Bomsel, 1997;Bouschbacher et al, 2008;Collins et al, 2000;Gupta et al, 2002;Hladik et al, 2007;Hu et al, 2000;Kawamura et al, 2000;Spira et al, 1996;Tan & Phillips, 1996;Zhang et al, 1999). In particular, two cell types are considered targets of HIV infection at the port of entry, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies using kidney cell cultures suggested that paracellular permeability to electrical currents and non-charged solutes may be regulated by different sets of tight junctional proteins. [39][40][41][42][43] If this is the case, given that multiple types of tight junctional proteins are expressed in human cervicovaginal mucosa, 9,[44][45][46] it is possible that EDTA treatment affected certain tight junction proteins that control small-molecule movement, but it did not affect those that control electrical current flux. Such a change in the organization of tight junction, in our opinion, is not comparable to the physical breaches that facilitate HIV-1 entry into the submucosal compartment, [47][48][49] due to the difference in size and the entry mechanism between HIV-1 and mannitol.…”
Section: Discussionmentioning
confidence: 99%